Blending Crowdvoting in Modern e-Learning Environments - Maletić, Marija; Barać, Dušan; Naumović, Tamara; Bogdanović, Zorica; Radenković, Božidar (International Review of Research in Open and Distributed Learning, 2019)
Given that the most students spend considerable time on social networks, many educational institutions use this habit as a basis for educational purposes. Increasing students’ active participation in learning activities is one of the main goals of education. The purpose of this research was to investigate to what extent crowdvoting techniques can increase students’ participation and interest in the e-learning process. Additionally, we set out to explore social networks as a medium for crowdvoting, contests, and collaboration among students. The research participants included 131 students in the information technologies area of the Faculty of Organizational Sciences, University of Belgrade who participated in contest related to their 3D modeling projects. Voting was performed via Facebook. The students voted for particular projects primarily based on the quality of the project itself. Additionally, the competition was an incentive for students to prove themselves to colleagues, but also to provide an opportunity for teamwork, additional engagement, and acquisition of new skills and knowledge. The research results indicate a generally positive attitude among students towards the competition and rewards.